Selected bacteria in sheep stool depending on breed and physiology state - Paulina Cholewińska; Natalia Szeligowska; Konrad Wojnarowski; Paulina Nazar; Monika Greguła-Kania; Andrzej Junkuszew; Witold Rant; Aurelia Radzik-Rant; Anna Marcinkowska; Robert Bodkowski (Scientific Reports, 2023)
Abstract One of the important factors influencing the microbial community of ruminants, besides environment or diet, are breed and physiology. Therefore, the purpose of this study was to assess these changes in the levels of basic microbial phyla and families. For this study, qPCR analysis was performed to determine the level of bacteria (Firmicutes, Bacteroidetes, Actinobacteria, Proteobacteria clusters and Clostridiaceae, Lactobacillaceae families) in the feces of ewes of three native Polish sheep breeds (Polish Lowland Sheep (PON), Świniarka Sheep (SW), and synthetic line BCP) at different physiological periods (conception, early pregnancy, lambing, end of lactation). The animals were kept in the same environment and were at the same age (2-years). The results showed a significant effect of both breed (p = 0.038) and physiological period (p < 0.05, p < 0.01) on the levels of bacteria analyzed. The breed showed differences across physiological periods. The influence of the race factor was noted primarily between the BCP synthetic line and the other two breeds (differences in terms of all analyzed clusters and families except Actinobacteria phyla). In the case of SW and PON, however, the observed differences were only at the level of Proteobacteria cluster and Clostridiaceae family. On the other hand, the early pregnant and lambing periods were the most microbiologically diverse in terms of the analyzed clusters and families of bacteria.